Effects of computer‐based training on procedural modifications to standard functional analyses. Issue 1 (31st October 2017) - Schnell, Lauren K.; Sidener, Tina M.; DeBar, Ruth M.; Vladescu, Jason C.; Kahng, SungWoo
Abstract : Few studies have evaluated methods for training decision‐making when functional analysis data are undifferentiated. The current study evaluated computer‐based training to teach 20 graduate students to arrange functional analysis conditions, analyze functional analysis data, and implement procedural modifications. Participants were exposed to training materials using interactive software during a 1‐day session. Following the training, mean scores on the posttest, novel cases probe, and maintenance probe increased for all participants. These results replicate previous findings during a 1‐day session and include a measure of participant acceptability of the training. Recommendations for future research on computer‐based training and functional analysis are discussed.